2013
DOI: 10.1007/s10741-013-9375-x
|View full text |Cite
|
Sign up to set email alerts
|

Viral genomes in the pericardial fluid and in peri- and epicardial biopsies from a German cohort of patients with large to moderate pericardial effusions

Abstract: The aetiology of pericardial effusion has been generally assessed by clinical work-up only, which leaves a large cohort of patients with "idiopathic" effusions virtually undiagnosed. In accordance with the ESC guidelines, this contribution intends to change this attitude. After therapeutic or diagnostic pericardiocentesis of 259 patients with large to moderate pericardial effusions, pericardial fluid, epicardial and pericardial biopsies, and blood samples were analysed by PCR for cardiotropic microbial agents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 31 publications
0
17
0
12
Order By: Relevance
“…The cause of acute pericarditis is idiopathic in the majority of cases but includes an immune-mediated process that is probably triggered by a viral infection in many cases. 16,17 Reasons for sex differences in pericardial inflammation are unknown, but experimental viral studies of myocardial inflammation have suggested that although genetic differences have some effect, sex hormones are major contributors for sex predisposition. 3, 18 Testosterone appears to play a major role in the development of myocarditis, because exogenous testosterone increases viral replication and inflammation in the heart and gonadectomy inhibits cardiac inflammation in experimental viral myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of acute pericarditis is idiopathic in the majority of cases but includes an immune-mediated process that is probably triggered by a viral infection in many cases. 16,17 Reasons for sex differences in pericardial inflammation are unknown, but experimental viral studies of myocardial inflammation have suggested that although genetic differences have some effect, sex hormones are major contributors for sex predisposition. 3, 18 Testosterone appears to play a major role in the development of myocarditis, because exogenous testosterone increases viral replication and inflammation in the heart and gonadectomy inhibits cardiac inflammation in experimental viral myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…The most common etiology was idiopathic in the studies of Sagristà-Sauleda et al [9] and Levy et al [10] (29% and 48%, respectively); and in the study of Corey et al [11] it was infectious causes (27%) including unusual agents such as M. pneumonia and M. avium-intracellulare. Of note, in a recent prospective registry of 259 patients, an autoreactive etiology was the leading diagnosis in 35%, followed by malignancy in 28%, and viral etiology in 14% of the cases [12]. These discrepancies seem to mainly result from how aggressively the etiologic investigation was carried out.…”
Section: Discussionmentioning
confidence: 99%
“…This is most relevant for autoreactive pericarditis. Since PCR for the identification of cardiotropic viruses in pericardial fluid was not carried out in the present study, these patients might have constituted part of the patients with idiopathic pericarditis [12,19]. In addition, analysis of tumor markers (CEA, CA 19-9 etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Przyczyną nawrotów w wielu przypadkach jest niewłaściwe leczenie pierwszego epizodu zapalenia osierdzia. U nawet 20% chorych po wykonaniu dodatkowych badań w materiale z płynu osierdziowego lub z samej tkanki oserdzia stwierdza się etiologię wirusową schorzenia [63].…”
Section: Nawracające Zapalenie Osierdziaunclassified
“…Zabiegi inwazyjne [206] umożliwiają wykonanie badania obrazowego (perikardioskopia) i uzyskanie materiału do badań molekularnych, histologicznych i immunohistochemicznych w celu identyfikacji czynnika etiologicznego oraz Poziom wiarygodności danych ustalenia mechanizmów patogennetycznych uszkodzenia osiedzia i nasierdzia [133]. W ten sposób możliwe jest też wykonanie procedury leczniczej, z podaniem leków do worka osierdziowego [63,204].…”
Section: Diagnostyka Inwazyjna I Leczenie Operacyjneunclassified